“TRANSLATION CHALLENGES OF RELIGIOUS METAPHORICAL PHRASEOLOGICAL UNITS FROM UZBEK INTO ENGLISH” (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
The present study is devoted to the analysis and elucidation of the challenges arising in the process of translating religious metaphorical phraseological units from Uzbek into English from both linguistic and cultural perspectives. The primary objective of this research is to identify the semantic, pragmatic, and conceptual discrepancies encountered in the translation of such units and to develop effective strategies for overcoming them. The study adopts a qualitative research design, employing comparative and contrastive analysis of selected Uzbek religious phraseological expressions alongside their English counterparts. The findings indicate that the principal difficulties and divergences in translation stem from culture-specific features, the inherent particularities of religious concepts, and the lack of direct equivalents in the target language. Moreover, the study reveals the risk of partial semantic loss or misinterpretation of metaphorical meaning during the translation process. Based on the results obtained, it is argued that the use of explanatory techniques, adaptation strategies, and functional equivalence significantly contributes to achieving translation adequacy. The conclusions demonstrate that the translation of religious metaphorical phraseologism constitutes a highly complex process, requiring from the translator not only advanced linguistic competence but also profound cultural awareness and sensitivity to religious nuances.